A Review of Problem-Solving Skills in Mathematics and Cooperative Learning among Primary School Students - Wan Sin, Yim; Johari Sihes, Ahmad; Hamidon, Mas (International Journal of Psychosocial Rehabilitation, 2020)
This paper reviews 10 published studies of Polya’s problem-solving strategy and 7 published studies of cooperative learning strategies in improving students’ problem-solving skills in mathematics. Mathematics is one of the compulsory subjects in primary school curricula. The occurrence of problem-solving skills in mathematics is a fundamental means of developing mathematical knowledge among students. In this review, the scope of each publication was examined thoroughly based on the effectiveness of Polya’s problem-solving strategy and the cooperative learning strategies that had helped students in achieving significantly better scores in mathematics.From this review, Polya’s problem-solving strategy is one of the effective strategies in enhancing primary students’ problem-solving skills. This strategy utilized Polya’s four phases of problem-solving, which start with understanding the problem, making a plan, carrying out the plan, and finally looking back at the completed solution. Cooperative learning strategies boosted primary students’ learning motivation and self-confidence and improved learning attitudes. This strategy involves grouping the students into a group of 4 to 6 who share the same goals to create a conducive learning environment. This review showed that by incorporating both Polya’s problem-solving strategy and cooperative learning strategies in creating an innovative teaching method, the problem-solving skills in mathematics among primary school students could be potentially enhanced to an unprecedented level.